Tinjauan Hukum Islam terhadap Penerimaan Dana Corporate Social Responsibility (CSR) dari Bank Konvensional - Hendra Wijaya; Sartini Lambajo; Dewi Indriani; Mutmainna Mutmainna (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2023)
This study aims to determine the nature of CSR and the law on the receipt and use of CSR funds in a review of Islamic law. The type of research used is descriptive qualitative (non-statistical) with a normative approach and library research methods. The results of the study show that CSR in an Islamic perspective is a business practice that has an Islamic ethical responsibility. The company incorporates Islamic religious norms which are marked by a sincere commitment to maintaining social contracts in its operations. Even though there is no limit to the amount of ownership of goods, services and profits, the ways to obtain and utilize them are limited by lawful and unlawful rules laid down by Shari'a. The view of Islamic law on receiving CSR funds from these conventional banks is detailed as follows. First, when viewed from the benefit in particular, leaving the funds/assistance provided and offered from these conventional banks, whether in the form of sweepstakes, prizes, or social responsibility programs, is better because it is something that comes from unlawful assets (usury). Second, however, if we look at the general benefits, it is permissible for us to take CSR assistance/funds from these conventional banks but not to use them for personal needs, namely to use them for public needs and benefits, such as for building bridges, repairing roads, making toilets. general, and so on.